OBESITY AS A RISK FACTOR FOR HEPATOBILIARY SYSTEM DAMAGE IN CHILDREN - Turaeva Dilafruz Holmuradovna; Garifulina Lilya Maratovna; Ashurova Maksuda Jamshedovna (Galaxy International Interdisciplinary Research Journal, 2022)
This review provides facts about liver changes in obesity as part of non-alcoholic fatty liver disease. The review contains the pathogenesis and morphological characteristics of the development of this condition, the features of the clinical picture, as well as methods of invasive and non-invasive diagnostics.